Generation of pro-and anti-inflammatory mediators after acetaminophen overdose in surviving and non-surviving patients. (15th August 2022) - Woolbright, Benjamin L.; Nguyen, Nga T.; McGill, Mitchell R.; Sharpe, Matthew R.; Curry, Steven C.; Jaeschke, Hartmut
Abstract: Acetaminophen (APAP) overdose causes liver injury in animals and humans. Although well-studied in animals, limited longitudinal data exist on cytokine release after APAP overdose in patients. The purpose of this study was to quantify concentrations of cytokines in APAP overdose patients to determine if early cytokine or complement measurements can distinguish between surviving and non-surviving patients. Plasma was obtained from healthy controls, APAP overdose patients with no increase in liver transaminases, and surviving and non-surviving APAP overdose patients with severe liver injury. Interleukin-10 (IL-10), and CC chemokine ligand-2 (CCL2, MCP-1) were substantially elevated in surviving and non-surviving patients, whereas IL-6 and CXC chemokine ligand-8 (CXCL8, IL-8) had early elevations in a subset of patients only with liver injury. Day 1 IL-10 and IL-6 levels, and Day 2 CCL2, levels correlated positively with survival. There was no significant increase in IL-1α, IL-1β or TNF-α in any patient during the first week after APAP. Monitoring cytokines such as CCL2 may be a good indicator of patient prognosis; furthermore, these data indicate the inflammatory response after APAP overdose in patients is not mediated by a second phase of inflammation driven by the inflammasome. Highlights: Multiple cytokines were measured in plasma of acetaminophen overdose patients. TNF-α, IL-1α, and IL-1β levels were not elevated over 5 days after an overdose. MCP-1 was drastically elevated in overdose patients with liver injury. Day 1 IL-10 and IL-6 and Day 2 MCP-1 levels correlated positively with survival. Complement C3 was depleted in all overdose patients but recovered only in survivors.